Beyond recovery: toward rights-based mental health care — A cluster randomized wait-list controlled trial of a recovery and rights training for mental health professionals with or without first person accounts - Eiroa-Orosa, Francisco José (Frontiers in Psychology, 2023)
Introduction Mental health models grounded in Recovery and Rights are driving the advancement of transformative care systems through multifaceted actions, which encompass Continuing Professional Development. The objective of this work is to evaluate a training activity developed through a participatory process that included people with lived experience of psychosocial distress, their relatives, and mental health professionals. Methods The training focused on alternatives to diagnosis, recovery principles, rights-based care, and peer support. The evaluation followed a cluster randomized wait-list controlled design. Four hundred eighty-eight health professionals from eight care centers were randomized to three experimental conditions: a wait list control, which underwent a one-month interval between the baseline assessment and the training activity, and two experimental groups, with or without first-person accounts, which accessed the training immediately after completing the baseline assessment. The dependent variables measured at all follow-ups were beliefs and attitudes toward mental health service users’ rights. One hundred ninety-two professionals completed at least one follow-up and were included in the analyses. Results We observed different evolutions of experimental and control groups with statistically significant differences for tolerance to coercion and total beliefs and attitudes scores. No differences were observed between the groups with or who attended training activities with or without first person accounts. Upon receiving the training activity, the control group had an evolution equivalent to the experimental groups. Discussion The results of this evaluation project provide compelling evidence for the need to expand recovery and rights training activities to reach a larger audience of mental health professionals These training activities hold the potential to positively influence the beliefs and attitudes of mental health professionals, ultimately contributing toward a better future for individuals with lived experience of psychosocial distress.